High-accuracy optical extensometer based on coordinate transform in two-dimensional digital image correlation. (January 2018) - Lv, Zeqian; Xu, Xiaohai; Yan, Tianhao; Cai, Yulong; Su, Yong; Zhang, Qingchuan
Highlights: A novel compensation method based on coordinate transform is proposed to remove measurement errors due to slant optical axis and out-of-plane motions. 3D positions can be reconstructed for points on the specimens with the coordinate transform algorithm. Simulation results come out that when the extensometer length is 400 pixels, the strain accuracy reaches 10 μ ε. The proposed compensation method enables 2D DIC to replace 3D DIC for full filed measurements in the measurements of plate specimens. Abstract: In the measurement of plate specimens, traditional two-dimensional (2D) digital image correlation (DIC) is challenged by two aspects: (1) the slant optical axis (misalignment of the optical camera axis and the object surface) and (2) out-of-plane motions (including translations and rotations) of the specimens. There are measurement errors in the results measured by 2D DIC, especially when the out-of-plane motions are big enough. To solve this problem, a novel compensation method has been proposed to correct the unsatisfactory results. The proposed compensation method consists of three main parts: 1) a pre-calibration step is used to determine the intrinsic parameters and lens distortions; 2) a compensation panel (a rigid panel with several markers located at known positions) is mounted to the specimen to track the specimen's motion so that the relative coordinate transformation between the compensation panel and the 2D DIC setup can be calculated using the coordinate transform algorithm; 3) three-dimensional world coordinates of measuring points on the specimen can be reconstructed via the coordinate transform algorithm and used to calculate deformations. Simulations have been carried out to validate the proposed compensation method. Results come out that when the extensometer length is 400 pixels, the strain accuracy reaches 10 μ ε no matter out-of-plane translations (less than 1/200 of the object distance) nor out-of-plane rotations (rotation angle less than 5°) occur. The proposed compensation method leads to good results even when the out-of-plane translation reaches several percents of the object distance or the out-of-plane rotation angle reaches tens of degrees. The proposed compensation method has been applied in tensile experiments to obtain high-accuracy results as well.